THE EFFECT OF MOTIVATION ON EMPLOYEE PERFORMANCE WITH REGIONAL PERFORMANCE BENEFITS AS INTERVENING VARIABLES IN THE REGIONAL INSPECTORATES OF PURWAKARTA - Tita Putri Astuti (JURNAL BISNIS STRATEGI, 2022)
Tita Putri Astuti, 2022. "The Effect of Motivation on Employee Performance with Regional Performance Allowances as an Intervening Variable at the Regional Inspectorate of Purwakarta Regency". Thesis. Master of Management Study Program, Faculty of Economics and Business, Indonesian education universityThe purpose of the study was to determine, analyze and explain the influence of the influence of motivation on employee performance with regional performance allowances US an intervention variable at the Regional Inspectorate of Purwakarta Regency.The research was conducted using descriptive verification methods, namely collecting, presenting and analyzing data using statistical tests. Comparing research results with existing theories and previous research. The sample used in this study were 77 employees of the Regional Inspectorate of Purwakarta Regency with the sampling technique using Disproportionary Stratified Sampling (sampling technique using certain criteria). The research instrument used a questionnaire and analyzed using path analysis.Calculations obtained that there is a relationship between Motivation (X) and Regional Performance Allowance (Y) indicated by the correlation coefficient value of 0.809. The relationship between Motivation(X) and Employee Performance (Z) are indicated by the correlation coefficient value of 0.866. The magnitude of the influence of motivation and regional performance allowances partially on employee performance is 17% (0.412 x 0.412) x 100% = 17% with a significant effect. The magnitude of the simultaneous influence of motivation and regional performance allowances on employee performance is 85.9% with a significant effect.